2008
DOI: 10.1152/physiolgenomics.00183.2007
|View full text |Cite
|
Sign up to set email alerts
|

Marsupial uncoupling protein 1 sheds light on the evolution of mammalian nonshivering thermogenesis

Abstract: Brown adipose tissue expressing uncoupling protein 1 (UCP1) is responsible for adaptive nonshivering thermogenesis giving eutherian mammals crucial advantage to survive the cold. The emergence of this thermogenic organ during mammalian evolution remained unknown as the identification of UCP1 in marsupials failed so far. Here, we unequivocally identify the marsupial UCP1 ortholog in a genomic library of Monodelphis domestica. In South American and Australian marsupials, UCP1 is exclusively expressed in distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 50 publications
3
74
0
Order By: Relevance
“…Hope et al, 1997). A recent study by Jastroch et al (Jastroch et al, 2008) found that in some marsupials (Monodelphis domestica and Antechinus flavipes) BAT expressing uncoupling protein 1 may be recruited transiently during early life and is lost in later life stages, whereas in S. crassicaudata it remains also during adult life stages. We found that body mass and specifically tail width, which is an indicator of fat storage in S. crassicaudata, did not differ between both rearing groups (Table1).…”
Section: Resting Metabolic Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Hope et al, 1997). A recent study by Jastroch et al (Jastroch et al, 2008) found that in some marsupials (Monodelphis domestica and Antechinus flavipes) BAT expressing uncoupling protein 1 may be recruited transiently during early life and is lost in later life stages, whereas in S. crassicaudata it remains also during adult life stages. We found that body mass and specifically tail width, which is an indicator of fat storage in S. crassicaudata, did not differ between both rearing groups (Table1).…”
Section: Resting Metabolic Ratementioning
confidence: 99%
“…It has been demonstrated in rats that continuous early life exposure to a cold environment induces a permanent and irreversible increase in brown adipose tissue (BAT) thermogenesis (Morrison et al, 2000), whereas when adult animals are exposed to cold (cold acclimation) the changes that occur in BAT are reversible when the animals are returned to normal temperatures (Vollmer and Skøtt, 2002). In small placental mammals, BAT is the main source for non-shivering thermogenesis (Andrew, 1978;Himms-Hagen, 1984;Wunder and Gettinger, 1996;Jastroch et al, 2008). In marsupials however the role of BAT is controversial.…”
Section: Resting Metabolic Ratementioning
confidence: 99%
“…In mammals, BAT can be found amongst Eutheria and in marsupials [18], but not in Monotremata [19]. For these species, BAT allowed the successful radiation to cold environments, providing an evolutionary advantage.…”
Section: Bat Evolutionmentioning
confidence: 99%
“…Phylogeny studies on available literature provide evidence for a long UCP1 branch that closely relates fish and marsupials to the large distanced eutherians ). Since adaptive non-shivering thermogenesis is not fully developed in marsupials, this divergent evolution can be interpreted as the acquisition of novel thermogenic functions in BAT (independently of shivering and locomotor activity) just after the split of eutherians from marsupial lineages ~150 million years ago (Jastroch et al 2008). However, it seems that most UCP1 orthologues are specifically expressed in metabolically active tissues with high lipid contents, which can be converted into fat-burning machines during adaptive thermogenesis and excessive feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UCP1 deficiencies increase the ageing susceptibility of mice to diet-induced obesity (Kontani et al 2005), whereas ectopical expression of UCP1 in genetically obese mice decreases adiposity and increases temperature and metabolic rates (Gates et al 2007). Less clear is the role of UCP1 in human obesity (Gonzalez-Barroso et al 2000), but even in marsupials overexpression of UCP1 in the archetypal BAT can be of relevance for the whole-body energy balance (Jastroch et al 2008). In fish, the number of analysed species is little representative of the phyla, but both this (gilthead sea bream study/superorder Acanthopterygii) and earlier studies in carp (superorder Ostariophysi) support a high expression level of UCP1 in liver and notably not in cells of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%